An anthropometric and physical profile of young Swiss alpine skiers between 2004 and 2011 - Gorski, T.; Rosser, T.; Hoppeler, H.; Vogt, M. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To describe the development of anthropometric and physical characteristics of young Swiss alpine skiers between 2004 and 2011, to compare them between age and performance-level groups, and to identify age- and sex-dependent reference values for the tests performed. Methods: The Swiss-Ski Power Test includes anthropometric measures and physical tests for coordination and speed, strength, anaerobic capacity, and endurance. The authors analyzed the results of 8176 tests performed by 1579 male and 1109 female alpine skiers between 2004 and 2011. Subjects ranged between regional and national level of performance and were grouped according to their competition age groups (U12, 11 y; U14, 12-13 y; U16, 14-15 y; U18, 16-17 y; U21, 18-20 y) and performance level. Results: A progressive increase in anthropometric measures and improvements in tests results with increasing age were found. For all tests, male athletes had better results than female athletes. Minor differences were observed in anthropometric characteristics between 2004 and 2011 (mostly <5%), while results of physical and coordinative tests showed significant improvements (up to more than 50% enhancement) or stability over the years. Differences between higher- and lower-level athletes were more pronounced in tests for lower-limb strength and anaerobic capacity. Conclusions: The presented profile of young Swiss alpine skiers highlights the improvements in different physical aspects along the maturation process and chronologically over a period of 7 y. Furthermore, reference values are provided for comparisons with alpine skiers or athletes from other sports.